Comprehensive landscape of the ST3GAL family reveals the significance of ST3GAL6-AS1/ST3GAL6 axis on EGFR signaling in lung adenocarcinoma cell invasion - Li, Jiaxuan; Long, Yiming; Sun, Jingya; Wu, Jiajun; He, Xiao; Wang, Simei; Wang, Xiongbiao; Miao, Xiayi; Huang, Ruimin; Yan, Jun (Frontiers in Cell and Developmental Biology, 2022)
Sialylation aberration has been implicated in lung cancer development by altering signaling pathways. Hence, it is urgent to identify the key sialyltransferases in the development of lung adenocarcinoma (LUAD), which is a common malignant subtype of non-small cell lung cancer. Herein, by systematically investigating the expression levels of ST3GAL family members in several public databases, we consistently found the frequent downregulation of ST3GAL6 in LUAD samples. Its downregulation is significantly negatively associated with stage, and significant reduced in Proximal-proliferative molecular subtype and predicts poor clinical outcomes. By protein-protein interaction network analysis and validation, we found that ST3GAL6 deficiency promotes LUAD cell invasiveness with the activated EGFR/MAPK signaling, accompanied by the elevated expression levels of matrix metalloproteinase 2 and 9, which can be partially reversed by EGFR inhibitor, gefitinib. Additionally, the ST3GAL6 level was positively regulated by ST3GAL6-AS1, an antisense long non-coding RNA to its host gene. The downregulation of ST3GAL6-AS1 also heralds worse prognosis in LUAD patients and promotes LUAD cell invasiveness, recapitulating the function of its host gene, ST3GAL6. Altogether, ST3GAL6-AS1-regulated ST3GAL6 is a frequently downregulated sialyltransferase in LUAD patients and negatively regulates EGFR signaling, which can serve as a promising independent prognostic marker in LUAD patients.